Effect of Dental Implant Diameter on Fatigue Performance. Part II: Failure Analysis - Shemtov-Yona, Keren; Rittel, Daniel; Machtei, Eli E.; Levin, Liran (Clinical implant dentistry and related research, 2014)
Purpose The purpose of this study was to perform fracture mode analysis for in vitro failed implants in order to evaluate the relation between the fracture mode obtained and the implants’ fatigue behavior. Materials and Methods Eighty fractured dental implants were analyzed after being tested for fatigue performance. A macroscopic failure analysis was performed, which evaluated and located the fracture modes obtained, followed by a microscopic failure analysis comprising a detailed scanning electron microscopy (SEM) fractographic analysis. Results Four distinctive fracture loci were identified and macrofracture mode analysis was performed, showing that all 5‐mm implants that fractured were fractured at the abutment neck and screw. In the 3.75‐mm group, 44.4% were fractured at the implant neck and 55.5% at the implants second thread. Fifty‐two percent of the 3.3‐mm fractured implants had it at the implants second tread and 48% at the implants third thread. The implant's metallographic sections revealed that the different fracture loci were located where thin metal cross sections and sharp notches coexist. Using SEM, we were able to characterize the failure micromechanisms and fatigue characterization as transgranular fracture and arrays of secondary parallel microcracks at relatively low magnifications and classic fatigue striations at much higher magnifications. Conclusions The results of this study indicate that proper implant design is crucial to ensure long‐term fatigue performance for dental implants. The combination of sharp notches (thread) and narrow metal cross section is quite deleterious for fatigue resistance.